The Protocol No. 16 To the echr and the advisory role of the European Court of Human Rights also in the light of a future and still uncertain italian ratification - Grieco, Cristiana (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This article discusses the first advisory opinion of the European Court of Human Rights under the Protocol No 16 to the ECHR at the request of the French Cour de Cassation, a few months after the same Protocol No 16 entered into force. The facts giving rise to the request for an opinión concern the question of recognition of a legal parent-child relationship established abroad following a surrogacy agreement by a heterosexual French couple, where only the father was biologically related to the children. The essay first discusses the content of the Court’s opinion and describes the main features of the ECHR’s new advisory function also by comparing it with the the preliminary ruling function of the Court of Justice of the European Union. The essay then examines the perspective of the future and at this stage still uncertain Italian ratification of the Protocol n.16.